2021
DOI: 10.1177/20530196211039275
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired life-like motile materials systems: Changing the boundaries between living and technical systems in the Anthropocene

Abstract: A current trend observed in the Anthropocene is the search for bioinspired solutions. Since it became possible to change the quality of the boundary between living and technical systems, more and more life-like technical products have been developed in recent years. Using five plant-inspired developments of motile technical systems for architecture and soft-robotics, we show how the boundary between living and technical systems undulates, shifts, perforates, blurs, or dissolves with increasing life-likeness. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 95 publications
(163 reference statements)
0
8
0
Order By: Relevance
“…Three cases of the study of biomimetic envelopes are shown in [ 103 ]. The first example is the Flectofin ® , a facade shading system that took as a role model the bird-of-paradise flower ( Strelitzia reginae ).…”
Section: Biomimicry In Responsive Envelopes and Applicationsmentioning
confidence: 99%
“…Three cases of the study of biomimetic envelopes are shown in [ 103 ]. The first example is the Flectofin ® , a facade shading system that took as a role model the bird-of-paradise flower ( Strelitzia reginae ).…”
Section: Biomimicry In Responsive Envelopes and Applicationsmentioning
confidence: 99%
“…However, some applications would still necessitate materials or composites that are not easily recyclable. For such systems, materials with features like self-healing or selfhardening for damage avoidance and longer life cycles would be beneficial (Terryn et al, 2017;Markvicka et al, 2018;Li et al, 2019;Meesorn et al, 2019;Terryn et al, 2020;Bai and Shepherd, 2021;Speck et al, 2022). Changing the systematic design into a compartmentalized modular design (Pfeifer et al, 2012;Pfeifer et al, 2007;McKenzie et al, 2018), in which parts can be interchanged or repurposed, would create even more sustainable soft robots.…”
Section: Figurementioning
confidence: 99%
“…Hinge-less compliant components contribute to the conservation of resources by reducing wear and tear and require little maintenance [ 56 , 57 ].…”
Section: Educational Trail About Biomimeticsmentioning
confidence: 99%
“…Hinge-less compliant components contribute to resource conservation by reducing wear and tear [ 56 , 57 ].…”
Section: Educational Trail About Biomimeticsmentioning
confidence: 99%